PENGARUH ORANG TUA, TEMAN, IKLAN TERHADAP PERILAKU MEROKOK SISWA DI SMA NEGERI 1 GUMAY TALANG KABUPATEN LAHAT - Santoso Ujang Effendi; Fikitri Marya Sari; Joni Pranata (Jurnal Sains Kesehatan, 2018)
Live activity that can be observed in teenager is smoking behavior. Smoking behavior is a very harmful behavior seen from different points of view from both yourself and others. The purpose of this survey was to investigate factors that related to the smoking behavior of teenager in SMA Negeri 1 Gumay Talang Kabupaten Lahat. The type of this survey is analytical survey using Cross Sectional design. The population of survey were 50 male student who smoked. The sampling is using Total Sampling techinique. Data colletion uses primary data and secondary data. Analyzed using Chi-Square test. The result of survey of 50 student three are 25 students (50%) who affect the parents, of 50 students there are 34 student (68%) who affect the friends, of 50 student there are 24 students (48%) who affect the ads, there is no relationship between the affect factor of parents with smoking behavior of teenager in SMA Negeri 1 Gumay Talang Kabupaten Lahat, there is a relationship between the affect of friend with smoking behavior of teenager in SMA Negeri 1 Gumay Talang Kabupaten Lahat, with the medium category, there is a relationship between the affect of ads, with smoking behavior of teenager in SMA Negeri 1 Gumay Talang Kabupaten Lahat, with the medium category. It is advisable for student, especially male students for not try smoking, don’t affected by parents and friends who smoke and also don’t affected by advertisements in the electronic and print media and also to increase knowledge about the dangers of smoking by reading a books or others that explain  the donges of smoking.   Keywords : advertisments, affect, friends, parents,  smoking behavior